2012
DOI: 10.1111/j.1442-2042.2012.03188.x
|View full text |Cite
|
Sign up to set email alerts
|

α1D/A‐adrenoceptor antagonist naftopidil for the male lower urinary tract symptoms associated with benign prostatic hyperplasia: Efficacy of dose increase therapy

Abstract: Abbreviations & AcronymsObjectives: To examine the efficacy of dose increase therapy in patients with lower urinary tract symptoms associated with benign prostatic hyperplasia who responded poorly to 50 mg/day of naftopidil. Methods: A total of 95 patients received 50 mg/day of naftopidil for 8 weeks. After this treatment period, they were divided into two groups: the poor responders were defined as those who either had an International Prostate Symptom Score-Quality of Life Ն4 or with an International Prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…[ 9 ] Recently, the efficacy of naftopidil dose increase therapy from 50 to 75 mg/day was evaluated for the patients who were ineffective in 50 mg/day. [ 10 11 ] However, it is unknown about the predictive factors which affect the efficacy of naftopidil dose increase therapy. Hence, we examined the predictive factors which affect the efficacy of naftopidil short-term therapy and dose increase therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] Recently, the efficacy of naftopidil dose increase therapy from 50 to 75 mg/day was evaluated for the patients who were ineffective in 50 mg/day. [ 10 11 ] However, it is unknown about the predictive factors which affect the efficacy of naftopidil dose increase therapy. Hence, we examined the predictive factors which affect the efficacy of naftopidil short-term therapy and dose increase therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There were some reports that the effective ratio of naftopidil monotherapy for 8∼12 weeks were 50.8%, 52.5% and 68.6%. [ 10 11 12 ] Therefore, it thought that this result was appropriate. Nevertheless, Mizusawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…Yamaguchi et al . showed that the dose increase to 75 mg/day in the patients who were responding poorly to 50 mg/day of naftopidil was a useful therapy of choice before switching to another α1‐blocker . There was no increase of the incidence of adverse events, even when the drug was increased in dosage.…”
mentioning
confidence: 99%
“…Yamaguchi et al . are to be congratulated for their well‐structured and consequently highly evaluated work on the efficacy of dose increase therapy with the α1D/A‐adrenoceptor antagonist, naftopidil, for the male lower urinary tract symptoms associated with benign prostatic hyperplasia.…”
mentioning
confidence: 99%